SYMBOLIC MEANING IN THE MOVIE DUA GARIS BIRU THE WORK OF GINATRI S. NOER AND THE INTERNALIZATION OF SEX EDUCATION - Andi Tenri Sua; Daud Rodi Palimbong; Andi Nurhabibi Marwil; Antika Utami Putri; Elihami Elihami (Universitas Negeri Makassar, 2024)
The research aims to find out the symbolic meaning of the film Dua Garis Biru by Ginatri S. Noer, the impact of early marriage and how to internalize sex education in the younger generation. This research uses a qualitative descriptive research design using Roland Barthes's Semiotic Analysis Method with connotation and denotation meanings. The subject of this study is the film Dua Garis Biru, with the object of the research is the symbolic meaning that is found in the film Dua Garis Biru Ginatri S.Noer's work (Bara and Bima) as the internalization of Sex Education in the younger generation. Data is collected through, observations, documentation and interviews using Rolland Barthes' semiotic analysis that emphasizes the observation of phenomena and requires strong instincts. Data analysis phases include data reduction, data presentation, and conclusion. As for the scientific implications that can be concluded through this research that the film. The film Dua Garis Biru portrays the consequences faced by two young individuals after engaging in sexual intercourse, significantly impacting their lives. It underscores the critical role of parents in their children's lives, particularly in communicating sexual information. The findings suggest that films with relevant content can effectively address and promote an understanding of sexual health issues among young audiences. This study contributes to the understanding of sex education in movies, illustrating how cinematic narratives can serve as educational tools for sexual health.